Innovation to Create a Healthy and Sustainable Food System: A Science Advisory From the American Heart Association. Issue 23 (4th June 2019) - Anderson, Cheryl A.M.; Thorndike, Anne N.; Lichtenstein, Alice H.; Van Horn, Linda; Kris-Etherton, Penny M.; Foraker, Randi; Spees, Colleen
Abstract : Current dietary intakes of North Americans are inconsistent with the Dietary Guidelines for Americans . This occurs in the context of a food system that precludes healthy foods as the default choices. To develop a food system that is both healthy and sustainable requires innovation. This science advisory from the American Heart Association describes both innovative approaches to developing a healthy and sustainable food system and the current evidence base for the associations between these approaches and positive changes in dietary behaviors, dietary intakes, and when available, health outcomes. Innovation can occur through policy, private sector, public health, medical, community, or individual-level approaches and could ignite and further public-private partnerships. New product innovations, reformulations, taxes, incentives, product placement/choice architecture, innovative marketing practices, menu and product labeling, worksite wellness initiatives, community campaigns, nutrition prescriptions, mobile health technologies, and gaming offer potential benefits. Some innovations have been observed to increase the purchasing of healthy foods or have increased diversity in food choices, but there remains limited evidence linking these innovations with health outcomes. The demonstration of evidence-based improvements in health outcomes is challenging for any preventive interventions, especially those related to diet, because of competing lifestyle and environmental risk factors that are difficult to quantify. A key next step in creating a healthier and more sustainable food system is to build innovative system-level approaches that improve individual behaviors, strengthen industry and community efforts, and align policies with evidence-based recommendations. To enable healthier food choices and favorably impact cardiovascular health, immediate action is needed to promote favorable innovation at all levels of the food system. Abstract : Supplemental Digital Content is available in the text.